Henry and Mudge and Annie's Perfect Pet: The Twentieth Book of Their Adventures - Rylant, Cynthia; Stevenson, Su=cie. (New York : Simon & Schuster Books for Young Readers, 2000)
Although Henry's cousin Annie likes his dog Mudge, when she gets her own pet she decides that a bunny will be perfect for her.
Keywords: Rabbits -- Fiction; Dogs -- Fiction; Pets -- Fiction; Cousins -- Fiction